2013
DOI: 10.1371/journal.pone.0079449
|View full text |Cite
|
Sign up to set email alerts
|

More Tweets, More Votes: Social Media as a Quantitative Indicator of Political Behavior

Abstract: Is social media a valid indicator of political behavior? There is considerable debate about the validity of data extracted from social media for studying offline behavior. To address this issue, we show that there is a statistically significant association between tweets that mention a candidate for the U.S. House of Representatives and his or her subsequent electoral performance. We demonstrate this result with an analysis of 542,969 tweets mentioning candidates selected from a random sample of 3,570,054,618,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(124 citation statements)
references
References 29 publications
2
103
0
2
Order By: Relevance
“…DiGrazia and colleagues have also used Twitter to discern voting intentions; their findings confirm those of Connover about the practical organisation of conservatives through social media in the US (Chew & Eysenbach, 2010;DiGrazia, McKelvey, Bollen, & Rojas, 2013). They point to the limitations of earlier studies but through an analysis of over ½ million tweets posted during 795 competitive election races in the US between 2010-12 found that social media has a role in indicating political behaviour.…”
Section: Methodsmentioning
confidence: 70%
“…DiGrazia and colleagues have also used Twitter to discern voting intentions; their findings confirm those of Connover about the practical organisation of conservatives through social media in the US (Chew & Eysenbach, 2010;DiGrazia, McKelvey, Bollen, & Rojas, 2013). They point to the limitations of earlier studies but through an analysis of over ½ million tweets posted during 795 competitive election races in the US between 2010-12 found that social media has a role in indicating political behaviour.…”
Section: Methodsmentioning
confidence: 70%
“…This is a fundamental limitation of this study in terms of the content of the data; we have not linked the Tweets to who people are or what people do in the offline world, thus all findings are based on how these behaviors are communicated online. Initial work assessing online and offline behavior has shown that reliable data about political behavior (candidates supported online and voting behavior) [32], and weight loss [65] are also validated in the offline world. As we discuss below, a comprehensive study that links the social media communications to offline behaviors should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…In the other group, we find studies using digital trace data as predictors of political events and phenomena or proxies for other more traditional measurement approaches in the social sciences, such as surveys (Barberá, 2015;DiGrazia, McKelvey, Bollen, & Rojas, 2013;Steinert-Threlkeld, Mocanu, Vespignani, & Fowler, 2015;Tumasjan, Sprenger, Sandner, & Welpe, 2010). Here, we find a strong prominence of studies concentrating on statistical predictions of various political outcomes based on signals found in digital trace data (see Hofman, Sharma, & Watts, 2017;Schoen et al, 2013).…”
Section: The Empiricist Challengedmentioning
confidence: 99%